The effect of organizational justice on employee performance by job satisfaction as an intervening variable - Jufrizen Jufrizen; Ega Sandra Kandhita (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Padang, 2021)
Organizational justice, job satisfaction and employee performance are an important thing to consider in managing employees. Good organizational justice must be considered because organizational justice can affect job satisfaction and performance which makes employees feel like they want to give their best effort and join the struggle together to achieve organizational goals. This study aims to see whether job satisfaction mediates the influence of organizational justice on employee performance in the field of expenditure budget and the secretariat at the regional financial and asset management agency of North Sumatra province. Sample of this research is all permanent employees of the regional office of the Directorate General of Treasury of North Sumatra province, which may be 84 people. The results showed that organizational justice had a positive and significant effect on the performance of the employees of the regional financial and asset management agency of North Sumatra province. Job satisfaction has a positive and insignificant effect on employee performance at the regional financial and asset management agency of North Sumatra province. Organizational justice has a positive and significant effect on job satisfaction of employees of the regional financial and asset management agency of North Sumatra province. Job satisfaction does not mediate the effect of organizational justice on employee performance